Effectiveness of ridge preservation on immediate implant placement in post-extraction patients with stage III/IV periodontitis : Efektifitas ridge preservation pada immediate implant placement pasien pascaekstraksi gigi dengan periodontitis stage III/IV - Kahar, Fachrun; Adam, Mardiana (Makassar Dental Journal, 2024)
In periodontitis cases with stage III/IV there will be mobility in the patient's dentition. The best option for replacing missing teeth is implants, especially immediate implants. The periodontitis condition requires further follow-up to achieve primary and secondary stability and improve the prognosis of the implant. The review was conducted using Google Scholar, Science Direct and Pubmed to find relevant articles for inclusion, then synthesised using the PRISMA guideline. 105 articles were found in the initial search and 3 articles were synthesised. Immediate implant placement can be performed in patients with stage III/IV periodontitis but ad-ditional care and follow-up is required compared to patients without periodontitis. It was concluded that immediate implants can be placed in patients with stage III/IV periodontitis if the periodontitis condition has been resolved and an evaluation of the ridge to be placed, as well as more intensive maintenance of oral hygiene.